Physical activity: the forgotten tool for type 2 diabetes management - Colberg, Sheri R. (Frontiers in Endocrinology, 2012)
Individuals who are currently sedentary, unfit, or overweight can benefit metabolically from simply taking breaks from sitting. Since avoidance of sedentary behavior appears to have a large impact on glycemic management, all individuals with type 2 diabetes should be encouraged to minimally engage in greater daily movement to better manage their diabetes and body weight. In addition, engaging in physical activity of any intensity (including low-intensity ones) likely positively impacts insulin action and blood glucose control acutely. Moreover, as long as total caloric expenditure during exercise is matched (i.e., total exercise dose), daily exercise may be done every other day instead with the same glycemic results, although at least 150 minutes of weekly physical activity is recommended. Both aerobic and resistance training are important for individuals with diabetes, and ideally a program that combines the two types of training should be undertaken to achieve maximal glycemic and other benefits. Once individuals have successfully implemented more daily movement into their lifestyle, they will be more likely to participate in structured forms of physical activity to gain additional benefits. All clinicians working with individuals with either type 2 diabetes or prediabetes should consider incorporating these suggestions into care plans to improve their patients’ glycemic management.